(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The article analyzes the features of public procurement in Ukraine and their role in the public finance system; the factors influencing their efficiency are investigated; identified problems that exist in Ukraine during tender procurement, as well as difficulties in the activities of controlling structures of the country in the field of public procurement The purpose of the article is to reveal the features and problems of public procurement in Ukraine and identify ways to overcome them, which, accordingly, will have a positive impact on the functioning of public finances in our country. The objectives of the article are to substantiate the directions of reforming the mechanism of public procurement in Ukraine, taking into account the experience of EU countries; identification of financial features of public procurement after the entry into force of the new version of the Law of Ukraine "On Public Procurement"; research of forms of financial responsibility of participants of public procurements in Ukraine and their efficiency. Public procurement is an important tool for regulating supply and demand for specific types of products, as they are the purchase of goods, works and services for public funds. Due to this, it is important to achieve efficient use of budget funds allocated for public procurement in Ukraine, which has not yet been achieved. Therefore, to increase the transparency and efficiency of these funds in our country, it is advisable to study the experience of EU member states, as the main task of reforming public procurement in our country is to implement an effective system in accordance with the principles and approaches applied by EU countries. should ensure financial efficiency and transparency of the procurement procedure. It is also necessary to analyze the changes that have taken place in public procurement after the introduction in 2020 of a new version of the Law of Ukraine "On Public Procurement", as along with the positive aspects are negative, which is manifested in the existence of corruption schemes in tenders. In addition, it is important to identify possible negatives in cooperation with the EU in the introduction of a localization mechanism in Ukraine for tender procurement.